Effectiveness of Hyoscine butyl bromide in shortening the first stage of labour – case series and review of literature. (2017)
Background: Prolonged labour from cervical dystocia or stasis is one of the common indications for caesarean delivery. Hyoscine N-butyl bromide (HBB), an anticholinergic and antispasmodic drug, has been found effective in shortening the first stage of labour with no adverse effects on feto-maternal outcomes. Case presentations: We present a series of 3 cases with apparent clinical evidence of prolonged labour but which later progressed to achieve vaginal delivery following an injection of HBB. Discussion: Relevant literatures explored revealed the clinical relevance and potential benefits of reviewing the use of HBB in our environment.